Outcome effects of single-set versus multiple-set training—An advanced replication study - Fröhlich, M.; Emrich, E.; Schmidtbleicher, D. (Research in Sports Medicine, 2010)
The starting point of this review is the assumption that single-set training (SST) can be regarded as an equal alternative to multiple-set strength training. On the basis of 72 primary studies, the meta-analysis dealt with the problem of single-set vs. multiple-set training (MST). The effectiveness of these training methods was examined depending on various interventions. Apart from qualitative decision aspects, the effectiveness was checked on the basis of effect size. Generally speaking, it can be stated that MST, depending on factors like age, training experience, duration of the study, etc., offers several advantages over single-set regimes (F = 3.71; df = 1; p = 0.06; eta2 = 0.02), especially when combined with periodization strategies, and it can be applied very successfully for increasing maximal strength in long-time effects. Therefore, the outcome effects of both methods are the same in short-time interventions. For longer-time interventions (F = 15.74; df = 1; p < 0.05; eta2 = 0.12) and for advanced subjects with the goal of optimizing their strength gain, however, multiple-set strategies are superior (F = 7.32; df = 1; p < 0.05; eta2 = 0.06).